EROSI PADA LAHAN HORTIKULTURA YANG DITANAMI WORTEL ( Daucus carrota L.) DI KELURAHAN RURUKAN KECAMATAN TOMOHON TIMUR - Cyndi S. Faizal; Meldi Sinolungan; Zetly Tamod; Tommy Sondakh (COCOS, 2013)
ABSTRACTThe type of soil in the research site is Andisol soil with clay texture. The Andisol soil characteristics is a dark color / black, gray, dark brown to yellowish. The soil derived from volcanic ashes from the eruption of the volcano. Therefore, this type of soil are found in the area around the volcano's slopes. Like the soil in this research is located on the slopes of Mount Mahawu. Although it has many advantages, but the ground Andisol also has many disadvantages. Andisol ground weakness is due to the loose structure and crumbly, the type of soil is very easy take by rainwater. Therefore, in this research, land conservation efforts in the form of plastic mulching. In this study the use of plastic mulch as a treatment, more soil erosion results in the use of plastic mulch plots compared to not using plastic mulch. This is due to the use of plastic mulch, most of the rain water does not infiltrated into the ground because it was blocked by the plastic mulch, causing greater runoff. Large land runoff causes soil erosion more bigger easily transported.Keywords : Erosion, Soil Conservation Technique, Holticulture, Carrot (Daucus carrota L.)